2021
DOI: 10.1177/21925682211001801
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Use of Drain Really Necessary for Posterior Lumbar Interbody Fusion Surgery? A Retrospective Case Series with a Historical Control Group

Abstract: Study Design: A retrospective case-control study. Objectives: The usefulness of a drain in spinal surgery has always been controversial. The purposes of this study were to determine the incidence of hematoma-related complications after posterior lumbar interbody fusion (PLIF) without a drain and to evaluate its usefulness. Methods: We included 347 consecutive patients with degenerative lumbar disease who underwent single- or double-level PLIF. The participants were divided into 2 groups by the use of a drain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These complications are associated with significant patient morbidity and can lead to increased health care costs and resource utilization [17]. However, the utility of postoperative drains in preventing wound complications and readmis-sions in spinal surgery has been controversial [14,18]. Our data suggest there may not be a benefit to drain usage in decreasing readmission rates, and the majority of drain variables were more accurate in predicting postoperative blood transfusions or anemia rather than hospital read- Regressions were performed with the corresponding drain variable in addition to age (years), length of stay (days), and number of levels fused as independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…These complications are associated with significant patient morbidity and can lead to increased health care costs and resource utilization [17]. However, the utility of postoperative drains in preventing wound complications and readmis-sions in spinal surgery has been controversial [14,18]. Our data suggest there may not be a benefit to drain usage in decreasing readmission rates, and the majority of drain variables were more accurate in predicting postoperative blood transfusions or anemia rather than hospital read- Regressions were performed with the corresponding drain variable in addition to age (years), length of stay (days), and number of levels fused as independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that inadequate postoperative drainage or the absence of a drainage tube may be a risk factor for SSEH after spinal surgery [8,9,16]. Nevertheless, several studies suggested that the use of drainage tubes could not reduce the incidence of SSEH [12,58,59]. The necessity of postoperative drainage remains controversial, but recently more high-quality studies [57,58,[60][61][62][63][64] have concluded that the usage of drainage tubes after spinal surgery cannot decrease postoperative complications, including the SSEH, even increase the need for perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is particularly relevant given that the use of wound drains varies widely among surgeons and has been postulated to prevent postoperative SEH. The overall conclusions on this practice have been mixed, and most have focused on the lumbar spine; 15,16 however, recent studies have associated postoperative drain placement with a wider spinal canal at the associated level 12 and decreased incidence and size of hematomas on postoperative day 1 by MRI. 17 Therefore, surgical drains should be used in multilevel surgery and those with multiple risk factors for PCEH.…”
mentioning
confidence: 99%